Using SWAT and SWAT-CUP for hydrological simulation and uncertainty analysis of the arid and semiarid watersheds (Case study: Zoshk Watershed, Shandiz, Iran) - Mohammad Reza Khaleghi; Seyed Hashem Hosseini (Applied Water Science)
Abstract The aims of this study are capability assessment of the SWAT model and SWAT-CUP software in hydrological simulation and evaluation of uncertainty of SWAT model in estimating runoff. In the modeling process, the basin was divided into 12 sub-basins and 294 hydrological units (HRUs). Model calibration and uncertainty analysis were performed using the sequential uncertainty fitting (SUFI2) algorithm for 2000–2006 and 2007–2010, respectively. Based on the sensitivity analysis results, the parameters are the USLE_P soil protection factor, wet soil density (SOL_BD), and CN among the most important parameters in determining the amount of output runoff. Among these factors, SCS-CN was recognized as the most sensitive parameter. Based on the results, the coefficients R2, bR2, and Nash–Sutcliffe index (NS) were 0.75, 0.59, and 0.67 for calibration period and 0.46, 0.24, and 0.42 for validation period. The results of the model showed the model performance is weak in the stage of calibration. This is due to the lack of accuracy and precision in the statistics available in the region, the lack of statistics on the amount of water collected from the upstream gardens of the area, as well as the lack of statistics on the existing springs. The model is therefore recommended for applications in arid and semiarid catchments within Iran with similar data. Due to the limited availability of hydrological data in Iran, this study has not assessed and compared the uncertainty related to the SWAT model of future runoff.